Implementation of Digital-Based Torajan Folk Story Media to Improve Students' Reading Interest - Tandiallo, Erianto; Tanduk, Rita; Dewi, Resnita (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
National Education functions to develop abilities and shape the character and civilization of a dignified nation to make the nation's life intelligent. The need to increase insight and knowledge certainly begins with the Literacy Movement which can be started by reading. However, according to UNESCO data, the reading interest of Indonesian people is very concerning, only 0.001%. This means that out of 1,000 Indonesians, only 1 person is an avid reader. Ironically, according to the Ministry of Communication and Information, although the interest in reading books is low, wear social data reveals that Indonesians can stare at gadget screens for approximately 9 hours a day. Gadget addiction by children today also has an impact on the social and cultural environment so that their understanding of local culture begins to fade. Thus, there is a need for innovative and interesting media to attract students' reading interest by highlighting local wisdom. The purpose of this study was to analyze the application of digital-based folklore media in increasing students' interest in reading. This study was conducted using a mix-method method on 20 fourth-grade students of SDN 1 Rantepao. The data collection techniques used were observation, interviews, tests, and documentation. The results of this study were an increase in students' interest in reading after using the media. Digital-based folklore by utilizing interactive technology and interesting visual elements is used as an alternative learning media to increase student participation in reading activities. This research is useful for other schools that want to use digital-based learning media as well as a forum for preserving culture.